Application of Emax model to assess the potency of topical corticosteroid products. Issue 3 (8th June 2022) - Rath, Seeprarani; Zvidzayi, Michael; Bon, Charles; Kanfer, Isadore
Abstract: The objective of this study was to compare the potencies of two topical corticosteroid products (TCPs) using the E max model to fit the skin blanching responses obtained from the US FDA's vasoconstrictor assay (VCA) and to illustrate the influence of formulation on potency. The potencies of two marketed TCPs, Dermovate® cream containing clobetasol propionate (CP) and Elocon® cream containing mometasone furoate (MF), were assessed using healthy human subjects. In order to investigate the influence of formulation and associated vehicle properties, the creams were compared with their respective topical corticosteroids (TCs) from a previously published study wherein the inherent potencies of those TCs were assessed using a validated VCA method. Whereas the inherent potency of MF ( E max = −94.45 ± 0.21) was found to be greater than CP ( E max = −58.80 ± 15.65), when formulated as creams, the TCP containing CP had a higher potency ( E max = −86.15 ± 0.17) than that containing MF ( E max = −42.61 ± 26.04). This reversal of potency may be attributed to the effect of formulation factors. The comparison of the potencies of TCPs with inherent potencies of their corresponding TCs confirmed the influence of formulation parameters on the potency of those products.